'I've got anxiety'. Issue 1 (9th April 2022) - Gipps, Richard G.T.
Abstract: Anxiety is today increasingly talked about as if it were a condition or illness from which one suffers. This obscures the sense in which it may be said to have a meaning, that meaning being that the self is currently ill‐equipped to handle its predicaments. It also obscures the sense in which anxiety's apt 'prevention' and 'treatment' most often come from education rather than from psychological medicine, in particular from those disciplines we style the humanities. This short reflection‐prompting piece unpacks the above claims from the perspective of the author's two professions: philosophy and clinical psychology.